HBR's 10 must reads on AI, analytics, and the new Machine Age (Harvard Business Review Press, 2023)
In this book, you'll learn how: data science, driven by artificial intelligence and machine learning, is yielding unprecedented business insights; blockchain has the potential to restructure the economy; drones and driverless vehicles are becoming essential tools; 3-D printing is making new business models possible; augmented reality is transforming retail and manufacturing; smart speakers are redefining the rules of marketing; and humans and machines are working together to reach new levels of productivity